Silver Platter - Berlin, Ellin (Doubleday & Company, Inc. Garden City, New York, 1957)
In 1868 John Mackay told his wife Louise that someday soon he would be "master and manager of the richest mines on earth"; she would have everything he had promised - " the whole damn world on a silver platter." In 1873 twenty -two years of mining, John Mackay found his mountain of silver - the heart of the Comstock Lode. Life of wife of John Mackay, developer of silver mines in the Comstock Lode.
Keywords: Mackay, Marie Louise Antoinette (Hungerford) -- 1843-1928; Silver mines -- Comstock Lode